Comparison Of Alternative Dispute Resolution (Adr) In The Uk In Contrast With Australia And Its Advantages For Iraq, Kurdistan - Agha, Hazhar Jawhar; Rasul, Yousif Mostafa; Shwani, Sarsam Khaleel; Zeroo, Fathi Zeroo (The journal of contemporary issues in business and government, 2021)
This dissertation aims to investigate and compare of ADR methods in the UK and in Australia by comparing some of the ADR methods as Arbitration, Mediation, Negotiation and Conciliation. Since, there are major differences and similarities between both of the systems in either country in terms of the time, cost, Compulsion and Voluntarism degree. AS, ADR is voluntary in the UK and compulsory in Australia there might be some advantages and drawbacks of utilizing ADR. As there is a great amount of communication locally and universally among the countries, some new kinds of problems could be made. In the manner even if the court could not be able to recover all the domestic disputes, the international disputes might arise. Therefore, government like Iraq and Kurdistan might look for the other alternatives for resolution the problems. However, this might need a good evaluation and grounds in terms of applying ADR systems. It is true that there are some other alternatives in Iraq and Kurdistan as such Sulh, Sharia and Musalaha. Nevertheless, the decision maker's award is most belonging to the religions, culture and custom rather than the law and this might not be decent most of the times for the parties. Therefore, as ADR forms are working well in the UK and Australia. Therefore, it would be good for countries as such Iraq to use these systems for resolving their domestic and international problems. Though, mixed system of law which include Sharia and law in Iraq and Kurdistan have been enlightened. For that, some important ideas have been summarized to explain the most suitable system for applying ADR in Iraq and Kurdistan, as they do not have these methods. Likewise, some proper recommendations such as, reading ADR methods in Iraq and Kurdistan Law Schools, providing a proper ground for practicing ADR, and supporting the use of ADR by the governments has been made for the Iraq and Kurdistan governments in order to use ADR systems.